Monitoring of parasite and virus infections of the European eel, Anguilla anguilla, in northern Germany. - Jakob, Eva (2009)
The aim of this thesis was to examine metazoan parasite communities and viral infections of European eel, Anguilla anguilla, from fresh water, brackish and marine localities in northern Germany. The here collected data shall help to evaluate the suitability of the studied localities for potential restocking purposes regarding the presence of pathogens. In Chapter I a comparative examination of the metazoan parasite communities of the European eel was conducted including measures of parasite diversity characteristics. Special focus was given on the prevalence and intensity of infection with the invasive swim bladder nematode Anguillicoloides crassus and the gill monogenean Pseudodactylogyrus spp. In all, 29 parasite species/taxa were found in 170 eels from six different sample sites. Parasite communities of European eels clearly exhibit the habitat preferences of their hosts, salinity-dependent specificities, and a clustering into fresh-water, brackish, and marine groups. The highly pathogenic parasite species Anguillicoloides crassus and Pseudodactylogyrus spp. were found at all sampling sites in fresh water and brackish water, with high prevalence. Therefore, the common practice of catching glass eels in river estuaries for restocking solely in inland waters as management measure for stock recovery should be critically considered. To set a baseline for future trend analyses and biodiversity considerations an updated and comprehensive literature review on prevalence and distribution of parasites of the European eel in European waters was conducted (Chapter II). The resulting checklist provides evidence for 161 parasite species/taxa from 30 countries. Special consideration was given to the distribution of the swimbladder nematode Anguillicoloides crassus. A map and table of first reported records as well as a survey map indicating all published localities of A. crassus documented in the checklist are provided. In Chapter III the prevalence of virus infections in European eels from natural habitats with differing ...